Gamification-Based Learning Analytics: Enhancing Student Motivation and Retention in Post-Pandemic Hybrid Classrooms - Greget Widhiati; Agus Waryanto (Education : Jurnal Sosial Humaniora dan Pendidikan, 2025)
The post-pandemic shift toward hybrid learning environments has introduced significant challenges in maintaining student motivation and retention. This study proposes an integrated model combining gamification and learning analytics to address these issues in higher education. A quasi-experimental design was employed, involving 64 undergraduate students divided into control and experimental groups over one academic semester. The experimental group engaged with a customized Moodle-based learning system featuring gamification elements—such as points, badges, and leaderboards—and real-time analytics dashboards powered by xAPI and Learning Record Stores. Quantitative data were collected using pretest-posttest instruments (MSLQ and SCEQ) and analyzed using paired and independent-samples t-tests, correlation analysis, and regression analyses. Qualitative insights from student interviews supported the quantitative findings. Results showed a statistically significant improvement in both motivation and retention among students exposed to the integrated system. The study contributes to the growing body of research on adaptive learning by demonstrating how combining motivational game mechanics with actionable data insights can enhance student engagement in hybrid classrooms. These findings have practical implications for digital pedagogy and institutional strategies in the evolving post-pandemic educational landscape.